Impact of previous disease-modifying treatment on effectiveness and safety outcomes, among patients with multiple sclerosis treated with alemtuzumab. Issue 9 (12th March 2021) - Pfeuffer, Steffen; Ruck, Tobias; Pul, Refik; Rolfes, Leoni; Korsukewitz, Catharina; Pawlitzki, Marc; Wildemann, Brigitte; Klotz, Luisa; Kleinschnitz, Christoph; Scalfari, Antonio; Wiendl, Heinz; Meuth, Sven G
Abstract : Objectives: Alemtuzumab is effective in patients with active multiple sclerosis but has a complex safety profile, including the development of secondary autoimmunity. Most of patients enrolled in randomised clinical trials with alemtuzumab were either treatment naïve or pretreated with injectable substances. Other previous disease-modifying treatments (DMTs) were not used in the study cohorts, and therefore, associated risks might yet remain unidentified. Methods: We retrospectively evaluated a prospective dual-centre alemtuzumab cohort of 170 patients. We examined the baseline characteristics as well as safety and effectiveness outcomes, including the time to first relapse, the time to 3 months confirmed disability worsening and the time to secondary autoimmunity. Results: The regression analysis showed that, among all previously used DMTs, the pretreatment with fingolimod (n=33 HRs for the time to first relapse (HR 5.420, 95% CI 2.520 to 11.660; p<0.001)) and for the time to worsening of disability (HR 7.676, 95% CI 2.870 to 20.534; p<0.001). Additionally, patients pretreated with fingolimod were more likely to experience spinal relapses (55% vs 10% among previously naïve patients; p<0.001) and had an increased risk of secondary autoimmunity (HR 5.875, 95% CI 2.126 to 16.27; p<0.001). Conclusion: In the real-world setting, we demonstrated suboptimal disease control and increased risk of secondary autoimmunity following alemtuzumab, among patients previously treated with fingolimod. These data can provide guidance for improving MS therapeutic management.